No association of skin-fold thicknesses and training with race performance in male ultra-endurance runners in a 24-hour run - Knechtle, B.; Knechtle, P.; Rosemann, T. (Journal of Human Sport & Exercise, 2011)
In male high-level long-distance runners over 10,000 m, a positive association between both the front thigh and medial calf skin-fold thickness and running performance has been demonstrated. It is assumed that the thickness of skin-folds of the lower limb is related to training in highly trained runners. We investigated in 22 male ultra-endurance runners in a 24-hour run the relationship between skin-fold thicknesses and race performance. The 22 runners achieved a total of 154 (47) km during the 24 hours, varying from 73.079 km to 231.956 km. No association for both the skin-fold thicknesses and the training variables with race performance could be demonstrated. Furthermore, skin-fold thicknesses showed no relationship with both volume and intensity during training. We must assume that in ultra-endurance runners in a 24-hour run, other variables such as motivation and nutrition must be associated with race outcome.